2018
DOI: 10.1515/pz-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Economic and social zones during the Late Neolithic/Early Bronze Age in Jæren, Southwest Norway. Reconstructing large-scale land-use patterns

Abstract: Zusammenfassung Basierend auf einer Untersuchung der ökologischen und archäologischen Hinterlassenschaften für Jæren, Südwest-Norwegen, wird vorgeschlagen, dass der Übergang zu einer agrar-pastoralen Wirtschaft und Gesellschaft am Übergang vom mittleren zum späten Neolithikum (2400–2350 v. Chr.) erfolgte und es in Folge zu einer raschen Strukturierung der besiedelten Kulturlandschaften kam. In den folgenden Jahrzehnten und Jahrhunderten entwickelte sich die Gesellschaft auf dieser Basis fort. >Eines der ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The age model showed that the establishment of arable farming based on the presence of cereals occurred ca. 200-300 years later than previously argued (Prøsch-Danielsen et al 2018;Prescott 2020). This demonstrates the value of statistically testing radiocarbon data to provide accurate estimates for archaeological processes and events.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The age model showed that the establishment of arable farming based on the presence of cereals occurred ca. 200-300 years later than previously argued (Prøsch-Danielsen et al 2018;Prescott 2020). This demonstrates the value of statistically testing radiocarbon data to provide accurate estimates for archaeological processes and events.…”
Section: Discussionmentioning
confidence: 77%
“…The establishment of an agro-pastoral economy represents a significant societal shift reflected in material culture, architecture and settlement patterns, and traits associated with traditional farming settlement, such as two-aisled long houses and tilled fields, are now present. A similar trajectory took place in southwestern Norway as well (Prøsch-Danielsen et al 2018). The emergence and spread of farming into different ecological niches indicates a flexible and mixed economy during the Late Neolithic and Bronze Age, based on crop growing, animal husbandry and the use of wild resources.…”
Section: Palynological Evidence For Early Farmingmentioning
confidence: 67%
See 2 more Smart Citations
“…Fishing, hunting and gathering were the main forms of subsistence in southern Norway until the final breakthrough of agriculture c . 2300 BC (Prescott, 2012; Prøsch-Danielsen et al, 2018). A significant increase in radiocarbon dates in general (Figure 2), and specifically from cereal grains, tilled fields and farmsteads, indicates a further expansion in farming from 2000 BC (Mjærum, 2020; Solheim, 2021).…”
Section: Human Impact On Holocene Forest Dynamicsmentioning
confidence: 99%